PENINGKATAN HASIL BELAJAR TEMATIK MENGGUNAKAN MODEL MIND MAPPING PADA SISWA KELAS IV SEKOLAH DASAR - Azhari, Muhammad; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is "How is the Improvement in the Learning Outcomes of Thematic Learning more Emphasized in Social Studies Using Mind Mapping Models in Fourth Grade Students of SD Negeri 14 South Pontianak?". This study aims to improve student learning outcomes in thematic learning more emphasis on social studies using the Mind Mapping model. This research uses a descriptive method. The form of research used collaborative classroom action research.. Data collection techniques used are direct observation and measurement techniques. Data collection tools used were observation sheets and learning achievement tests. This research was conducted in 3 (three) cycles. The results obtained are 1)The ability of teachers to plan a thematic learning implementation plan is emphasized more on social studies using Mind Mapping models with an average score of cycle I namely, 3.11, cycle II 3.22, and cycle III 3.52. .2)The ability of teachers to implement the Thematic Learning Implementation Plan is emphasized more on social studies using Mind Mapping models with an average score of cycle I namely, 3.28, cycle II 3.39, and cycle III 3.66. 3)Student learning outcomes in thematic learning are emphasized more on social studies using Mind Mapping models with an average value of cycle I of 65.14, cycle II 69.72 and cycle III 75.29. The data obtained shows that using the Mind Mapping model in thematic learning is emphasized more on social studies can improve student learning outcomes in class IV SD Negeri 14 South Pontianak.Â Keywords : Improvement, Learning Outcomes, Mind Mapping Learning Models